2022
DOI: 10.2147/ccid.s362785
|View full text |Cite
|
Sign up to set email alerts
|

Triple Cross-Linked Hyaluronic Acid Based on Tri-Hyal Technique Has More Durable Effect on Dermal Renewal

Abstract: Background Hyaluronic acid (HA)-based fillers are applied to treat facial wrinkles and volume loss. Many efforts have been made to improve properties of HA to prolong the duration in aesthetic indications. A new cross-linking technique called “Tri-Hyal”, could make HAs to achieve desired rheological characteristics. HAs synthesized by Tri-Hyal are triple cross-linked and sustained-release, which could increase duration of promoting skin rejuvenation after injection. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several advantages have been discussed regarding this manufacturing technology. Exemplary, studies have suggested the minimization of cross‐linking agent that could reduce potential toxicity, the slow release of free HA which can promote extra‐cellular matrix production by fibroblasts and longer‐lasting stimulation of dermal growth 27–29 . However, more basic science research needs to be conducted to further define the molecular mechanisms by which soft‐tissue fillers manufactured using Tri‐Hyal technology improve skin quality.…”
Section: Discussionmentioning
confidence: 99%
“…Several advantages have been discussed regarding this manufacturing technology. Exemplary, studies have suggested the minimization of cross‐linking agent that could reduce potential toxicity, the slow release of free HA which can promote extra‐cellular matrix production by fibroblasts and longer‐lasting stimulation of dermal growth 27–29 . However, more basic science research needs to be conducted to further define the molecular mechanisms by which soft‐tissue fillers manufactured using Tri‐Hyal technology improve skin quality.…”
Section: Discussionmentioning
confidence: 99%
“…The ART FILLER® line is a group of fillers produced with Trihyal technology, meaning they have long chain, very-long chain, and free non-crosslinked HA in their composition [34,35]. The Universal filler was chosen as the control group, as it is the most used one out of the five and the most versatile.…”
Section: Discussionmentioning
confidence: 99%